Separate Collection of Bio-Waste in General Areas of University Centers - Torrijos, Verónica; Dono, Martina; Soto, Manuel (Journal of Sustainability Perspectives, 2023)
Traditionally, the separate collection of different fractions of waste in university centers was limited to the collection of paper/cardboard and packaging waste, while the collection of bio-waste was introduced only for dining and cafeteria services. It was based on the consideration that in general areas of the centers, such as classrooms, corridors, administrative areas, or offices, organic waste was not generated. However, eating habits and lifestyles have been changing and food remains becoming more frequent in these areas. The inspections carried out in the UDC in 2015 showed that 25% of the waste belonged to the bio-waste category, and subsequent inspections indicated that in some cases it may constitute the main waste fraction. Having verified this fact, the conclusion was that the intra-center waste segregation model should be revised, introducing a specific collector for bio-waste in all areas of the university centers. This communication describes the separate collection model and presents the results achieved in five centers of the UDC. The results achieved were very positive, approaching or exceeding in most cases the threshold of 85% correct content in the bins, a value that is considered minimum to classify it as a separate collection for quality recycling. The capture of materials for recycling exceeded 70% of the waste generated.